Digital Technologies in Healthcare Management: A Study of Influence of National Culture for Adoption of Electronic Health Records in India and Australia - Singh, Harman Preet; Kumari, Radha (Archives of Business Research, 2023)
In the emerging healthcare landscape, digital technologies like electronic health records (EHRs) could play a vital role in healthcare management. While developed nations like Australia have taken the lead in implementing EHRs, developing nations like India, have lagged. Prior research in developing and developed countries has mainly focused on government policy, interoperability, standardization, security, technological infrastructure, and finance as EHR adoption factors, but the influence of national culture has remained unexplored. This study addresses this gap in the literature by comparing the influence of national culture on EHR adoption in India (a developing nation) and Australia (a developed nation). In this study, Hofstede's cultural dimensions were utilized to determine the influence of national culture. The assessment of India revealed that the adoption of EHRs could be influenced by the use of EHRs by respectable healthcare providers, the commitment and support of top management, and the education and training of healthcare managers to minimize risks connected with the use of EHRs. On the other hand, the adoption of EHRs in Australia may be influenced by professional involvement and discussion of the benefits of EHRs, business profitability, timely financial outcomes, and education and training of healthcare managers to understand the benefits of EHRs adoption.